Kuršėnų kalendorių muziejaus kalendorių rinkinys - Lukienė, Sigita (Knygotyra, 1997)
The result of the work of local enthusiasts and their helpers over 16 years, the calendars come from various countries (Russia, Israel, Latvia, Sweden, Switzerland, Finland, Great Britain, New Zealand, Mauritania, Tanzania, Italy) and cover different topics (nature, traditions, food, historical events, art, travels, etc.). Some of them are Lithuanian calendars from the first half of the twentieth century. A special classification has been created to maintain the collection.